Internal biliary drainage superior to external biliary drainage in improving gut mucosa barrier because of goblet cells and mucin-2 up-regulation. Issue 3 (31st May 2018) - Tang, Xuechan; Ma, Weiping; Zhan, Weirong; Wang, Xin; Dong, Huan; Zhao, Hongjing; Yang, Lin; Ji, Cuiying; Han, Qing; Ji, Chenguang; Liu, Hongqun; Wang, Na
Abstract : Backgroud: Obstructive jaundice increases intestinal permeability, but the pathological mechanisms remain obscure, which results in debates about the necessity of performing preoperative biliary drainage in patients with obstructive jaundice. Mucin-2 (MUC2) and goblet cells regulated by bile acids play an important role in maintaining the function of intestinal mucosal barrier. The present study was to investigate the role of goblet cells and MUC2 in obstructive jaundice and evaluate the effect of biliary drainage on intestinal permeability. Study design: We enrolled patients with malignant biliary obstruction and controls. We also did animal studies with four groups of rats: sham operation, obstructive jaundice, internal biliary drainage, and external biliary drainage. Histopathological analysis, biochemical measurement, and electron microscopy examination were done on pertinent samples. Results: Compared with the control group, the small intestinal mucosa was significantly damaged; goblet cells and MUC2 were significantly decreased and serum endotoxin level was significantly increased in patients and rats with obstructive jaundice. Biliary drainage, especially internal biliary drainage, significantly increased goblet cells and MUC2 and attenuated the damage of small intestinal mucosa. Conclusions: In obstructive jaundice condition, goblet cells and MUC2 were reduced which were involved in the damage of intestinal mucosa barrier; biliary drainage increased goblet cells and MUC2, repaired mucosa layer and restored the intestinal mucosa barrier function.